Shared leadership in tertiary care: design of a simulation for patient safety decision-making in healthcare management teams. (16th September 2020) - Aufegger, Lisa; Soane, Emma; Darzi, Ara; Bicknell, Colin
Abstract : Introduction: Simulation-based training (SBT) on shared leadership (SL) and group decision-making (GDM) can contribute to the safe and efficient functioning of a healthcare system, yet it is rarely incorporated into healthcare management training. The aim of this study was design, develop and validate a robust and evidence-based SBT to explore and train SL and GDM. Method: Using a two-stage iterative simulation design approach, 103 clinical and non-clinical managerial students and healthcare professionals took part in an SBT that contained real-world problems and opportunities to improve patient safety set within a fictional context. Self-report data were gathered, and a focus group was conducted to address the simulation's degree of realism, content, relevance, as well as areas for improvement. Results: Participants experienced the simulation scenario, the material and the role assignment as realistic and representative of real-world tasks and decision contexts, and as a good opportunity to identify and enact relevant tasks, behaviours and knowledge related to SL and GDM. Areas for improvement were highlighted with regard to involving an actor who challenges SL and GDM; more preparatory time to allow for an enhanced familiarisation of the content; and, video debriefs to reflect on relevant behaviours and team processes. Conclusions: Our simulation was perceived as an effective method to develop SL and GDM within the context of patient safety and healthcare management. Future studies could extend this scenario method to other areas of healthcare service and delivery, and to different sectors that require diverse groups to make complex decisions.